Are birds important pollinators of sago palm, Metroxylon sagu Rottb.? - Niez, Vanessa Mar M. (2004)
Birds species associated with flowering sago palms in three sampling areas of Agusan del Sur were studied. Ten birds species were observed from three flowering sago palms. Of these, four species were identified as foragers, namely: Nectarinia jugularis. Nectarinia sperata, Loriculus philippensis, and Dicaeum trogonostigma while six species were classified as visitants, namely: Alauda gulgula, artamus leucorhynchus, Lalage nigra, Corvus macrorhynchos, pycnonotus goiavier and Hypsipetes philippinus. Regardless of foraging species, the highest relative abundance was 58 individual birds. The feeding rate was from 49 to 55% per day indicating a continuous substantial consumption of nectars by foraging birds. The average foraging bout was 1.83 min. per day, a relatively long period spent by a foraging bird on the palm, indicating sago as an important source of nectar. All three foraging bird species were consistently observed in all sample palms except L. philippensis which means to be restricted to the undisturbed forest. Activity patterns of the foraging birds were highly correlated with time period. The peak of bird activity was between 12:00 noon and 3:00PM which coincided with the complete opening of sago flowers. However, no pollens were isolated from the body parts of twelve birds captured, suggesting that the birds are commensals. Thus, this study did not elicit birds as important pollinators of sago palm